Cj0440c Affects Flagella Formation and In Vivo Colonization of Erythromycin-Susceptible and -Resistant Campylobacter jejuni - Hao, Haihong; Fang, Xia; Han, Jing; Foley, Steven L.; Wang, Yulian; Cheng, Guyue; Wang, Xu; Huang, Lingli; Dai, Menghong; Liu, Zhenli; Yuan, Zonghui (Frontiers in Microbiology, 2017)
Campylobacter jejuni is one of the most common foodborne pathogen worldwide. A putative transcriptional regulator, Cj0440c, was up-regulated in the erythromycin-resistant C. jejuni, however the precise role of Cj0440c is yet to be determined. The aim of this study was to determine the biological functions of Cj0440c. The Cj0440c isogenic mutants were constructed from erythromycin-susceptible C. jejuni NCTC 11168 (S) and -resistant C. jejuni 68-ER (R), designating as SM and RM, respectively. The isogenic Cj0440c mutants (SM and RM) and parental strains (S and R) were subjected to microarray and qRT-PCR analysis to examine the transcriptional profile changes contributed by Cj0440c. The antimicrobial susceptibility, flagellar morphology, in vitro growth and in vivo colonization in chickens were carried out to analyze the biological function of Cj0440c. The results showed that 17 genes were down-regulated in SM compared to S, while 9 genes were down-regulated in RM compared to R. The genes with transcriptional change were mainly involved in flagella biosynthesis and assembly. Using transmission electron microscopy, we found that the filaments were impaired in SM and lost in RM. The chicken colonization experiments showed that Cj0440c mutants (SM and RM) had reduced colonization ability in chickens when compared with corresponding parental strains (S and R). In conclusion, Cj0440c regulates flagella biosynthesis and assembly, and consequently affect the in vivo colonization of erythromycin-susceptible and -resistant C. jejuni.